Kingella denitrificans as a Mimicker of Neisseria meningitidis in Carriage Surveillance - Delly Chipta Lestari; Puspa Andhia Kemalasari; Rifka Kamila; Chesya Ejoli; Wisnu Tafroji; Ibnu Agus Ariyanto; Selvi Nafisa Shahab; Bebby Shelby; Alana Arumsari (Al-Hijrah Indonesia, 2026)
Background: Meningitis caused by Neisseria meningitidis remains a significant public health concern. A carriage study is crucial for understanding the distribution of Neisseria meningitidis serogroups in the community. The presence of Kingella denitrificans may lead to misidentification as N. meningitidis due to phenotypic similarity on blood agar. However, the prevalence of K. denitrificans in nasopharynx and oropharynx remains unclear. Objective: This study aimed to determine the prevalence of K. denitrificans as a mimicker of N. meningitidis in a carriage surveillance setting and to evaluate the role of MALDI-TOF MS in ensuring accurate bacterial identification. Methods: A cross-sectional study was conducted from September to December 2025 among unvaccinated adults in Jakarta with meningococcal disease. Oropharyngeal and nasopharyngeal swabs were collected and cultured on VCNT-supplemented blood agar. Preliminary identification was performed using colony morphology, Gram staining, and oxidase and catalase tests. Definitive identification was carried out using MALDI-TOF MS. Results: Among 228 participants, 11 (4.8%) carried Kingella spp. in the nasopharynx and/or oropharynx. All carriers were females aged 19–33 years (median age: 25 years). The isolates exhibited colony morphology similar to N. meningitidis, potentially leading to misidentification. However, they could be differentiated by their Gram staining morphology and catalase test results. MALDI-TOF MS identified 5 of 11 isolates (45.5%) as K. denitrificans with high-confidence log scores. Conclusion: K. denitrificans phenotypically might mimicked N. meningitidis in carriage surveillance but can be distinguished with Gram staining. The integration of MALDI-TOF MS is essential to improve diagnostic accuracy and prevent false-positive results. Further studies are needed to assess the feasibility of implementing this technology in resource-limited settings.